IMPACTS OF CONSTRUCTION RISKS ON COSTS IN LEED-CERTIFIED PROJECTS - Gurgun, Asli Pelin; Arditi, David; Vilar, Pablo Casals (COLLEGE PUBLISHING, 2016)
Construction according to green principles rather than traditional methods poses a new set of risks to project participants. These risks should be appropriately identified and managed in order to prevent cost overruns. This study aims to identify construction risks and their cost impacts in LEED-certified projects. For this purpose, thirteen risks were identified based on a literature survey and were categorized under four groups of issues: (i) consultant, contractor and subcontractor, (ii) material, product and process, (iii) legal, regulatory and contractual, and (iv) financial and economic. A survey was then administered to green building design and construction practitioners in the U.S. to assess the likelihood of occurrence of these risks and their respective impacts on project cost. According to the survey results, the risks associated with consultant, contractor and subcontractor issues have the highest expected impact on costs. The top five risk factors were determined as (1) contractors and subcontractors agreeing to standards that are not within their expertise and competence, (2) high cost of certification, (3) lack of expertise in new products/technologies, (4) doubts about the long-term viability and performance of new and untested products, materials and technologies, and (5) inadequate definition of project parties' contractual roles and responsibilities. Mitigating the cost impact of risks is of great value to owners and designers and contractors. Recognizing the risks associated with LEED-certified projects and their cost impacts can be of benefit to all practitioners.
Keywords: green construction; LEED certification; risk; cost; green risk management; DELAY; MANAGEMENT; LESSONS; Architecture